National Family Policies and Mothers’ Employment: How Earnings Inequality Shapes Policy Effects across and within Countries - Hook, Jennifer L.; Paek, Eunjeong (American sociological review, 2020)
Although researchers generally agree that national family policies play a role in shaping mothers’ employment, there is considerable debate about whether, how, and why policy effects vary across country contexts and within countries by mothers’ educational attainment. We hypothesize that family policies interact with national levels of earnings inequality to differentially affect mothers’ employment outcomes by educational attainment. We develop hypotheses about the two most commonly studied family policies—early childhood education and care (ECEC) and paid parental leave. We test these hypotheses by establishing a novel linkage between the EU-Labour Force Survey and the Current Population Survey 1999 to 2016 (n = 23 countries, 299 country-years, 1.2 million mothers of young children), combined with an original collection of country-year indicators. Using multilevel models, we find that ECEC spending is associated with a greater likelihood of maternal employment, but the association is strongest for non-college-educated mothers in high-inequality settings. The length of paid parental leave over six months is generally associated with a lower likelihood of maternal employment, but the association is most pronounced for mothers in high-inequality settings. We call for greater attention to the role of earnings inequality in shaping mothers’ employment and conditioning policy effects.